Attitude of students and teachers of the Department of Pediatrics towards information and communication technology (ICT) - Reátegui Guzmán, Luis Américo (2015)
Introduction: Information and communication technology (ICT) has influence in education as it is an access tool to wealth of information. Though use in the teaching-learning process in educational institutions has not been significant. Objective: To determine attitude of students and teachers to use of ICT. Design: Non-experimental cross-sectional, correlational, quantitative study. Setting: Department of Pediatrics, School of Medicine, Universidad Nacional Mayor de San Marcos, Lima, Peru. Participants: Students and teachers. Interventions: Likert scale was implemented. Analysis of descriptive statistics, frequency distributions and central tendency measures were used. Results: Teachers attitude towards ICT was more favourable (86%) compared to students’ (76%). Conclusions: Teachers attitude to ICT was more favourable than students’. It is expected that this study will contribute to improvement in ICT-use decision, teachinglearning process and students’ attitude towards use of ICT.